Family and Kinship Relations Among Van Kyrgyz - N. A. Isabaeva (Научный диалог, 2022)
The folk traditions and family ties among the Van Kyrgyz, who settled from the Pamir region of Afghanistan in the Eastern part of Turkey, are considered. The purpose of the study is to analyze how the Kyrgyz traditions and customs have been preserved after 40 years of living in Turkey after the resettlement of the Kyrgyz from their homeland of the Pamirs. The novelty of the study lies in the appeal to previously unpublished in Russia studies of Turkish scientists who wrote about the history of the Van Kyrgyz, as well as to ethnographic data that the author collected over 5 years. It is noted that the Van Kyrgyz throughout their history, before settling in Turkey, were influenced by the culture of many other neighboring peoples. The reasons are indicated, among which are the constant nomadic lifestyle and close relations with the Kashkar Uighurs, contact with the culture of local Tajik and Afghan tribes in the Pamirs, life in Pakistan, etc. The impact of migration on the culture of the Van Kyrgyz and the preservation of national values is analyzed. The similarity of the traditions of the Kyrgyz of modern Kyrgyzstan and the Van Kyrgyz is being studied.